Hagop Tcholakian, History of the Armenian School in Syria, vol 1, vol 2, Yerevan, 2021. - Ghanalanyan, Tigran (History and Culture, 2022)
The review refers to the two-volume work “History of the Armenian School in Syria”, authored by Doctor of History Hagop Tcholakian. The Syrian-Armenian school is comprehensively studied in this work, from its origin to the present day. This fundamental work helps to visualize not only Syrian Armenian educational life, but also demographic, geographic, socio-cultural, political aspects.